Brittle porous material mesovolume structure models and simulation of their mechanical properties; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Smolin I. Yu. Igor Yurievich; Eremin M. O.; Makarov P. V.; Evtushenko E. P.; Kulkov S. N. Sergey Nikolaevich; Buyakova S. P. Svetlana Petrovna (2014, 2014)
Title screen